Conference Report: From challenges to solutions. (April 2011) - Abbott, Richard W; Gordon, Ben; van Amsterdam, Peter; Lausecker, Berthold; Brudny-Kloeppel, Margarete; Smeraglia, John; Romero, Fernando; Globig, Susanne; Golob, Michaela; Knutsson, Magnus; Herling, Christian; Vieser, Eva; et al.
The European Bioanalysis Forum is a bioanalytical nonprofit organization comprised of European pharmaceutical companies (27 members to date) and currently expanding to include CROs as well. The European Bioanalysis Forum provides a broad European bioanalytical network for the discussion of scientific, technological and regulatory topics of bioanalytical interest. The 3rd Annual Open Symposium was again much anticipated after the two previous successful meetings. The symposium included sessions on thinking outside the ''commodity'' box, bioanalytical challenges with blood, global harmonization, assay platforms, dried blood spots, immunogenicity, matrix effects, anomalous results, biomarkers and two plenary technology sessions hosted by the Platinum sponsors. Experts and key opinion leaders were invited as guest speakers. A total of 424 delegates registered from 113 companies representing a large percentage of the European bioanalytical community. In addition to 48 oral presentations, 88 posters were presented and there was a vendor exposition of 40 companies.